(untitled) (Acta Scientiarum. Animal Sciences, 2015)
The ingestive behavior of crossbred heifers grazing on stargrass pasture was managed at two levels of light interception and two levels of post-grazing residual height. The experiment was conducted at Pesagro (Seropédica, Rio de Janeiro State) between April 2012 and January 2013. The grazing (GT), rumination (RT) and idling (IT) times were evaluated every 10 minutes throughout a 24-hour period. Forage samples were collected for the analysis of chemical composition and for leaf:stem ratio determination. Dry bulb, wet bulb and black globe temperatures were evaluated every hour along with the relative humidity, during grazing to characterize the environment and calculate the Black Globe Humidity Index (BGHI). The mean grazing time (6 hours) was inversely related to sward height. The rumination time was associated with lignin content, in autumn and spring. The mean idle time (9 hours) was related to the grazing time. Animals became tolerant to climatic variations, as GT, RT and IT showed no temporal variations. On the other hand, the sward structure and its chemical characteristics showed greater influence on the ingestive activities of cattle grazing on pasture.